مجلس المحاسبة ودوره في مكافحة الفساد - • السعيد علي صوشة إدريس يعيش (جامعة المسيلة, 2022)
مجلس المحاسبة الجزائري هيئة عليا للرقابة المالية حديث النشأة ،أستحدث بموجب القانون 80-05 بناءً على دستور 1976 ، منح صلاحيات الرقابة المالية المحاسبية بغية الإشراف على رقابة الأعمال المالية للمؤسسات والإدارات العمومية التي منحه القانون متابعتها ، هذه الصلاحية مزدوجة بين القضائية والإدارية . ليعدل النص المتعلق به سنة 1990 ويلغي الرقابة القضائية من المهام الموكلة إليه، وجاء تعديل 1995 بنص الأمر 95-20 الساري الى يومنا هذا والذي أعاد له ممارسة الرقابة القضائية ، وهو ما وسعه تعديل 2010 ثم التعديل الدستوري لسنة 2016 وأكد على دستوريته كمؤسسة واسعة الصلاحيات في الرقابة المالية التعديل الدستوري الأخير 2020 وفقا للمادة 199 منه. وهو مؤسسة تتمتع بالاستقلال المالي والإداري وتخضع جميع المؤسسات العمومية في إطار منظومة النصوص القانونية السارية لرقابته بصفة إلزامية ،مع وجوبية تقديم حساباتها المالية السنوية أمامه، وفي حالة الإخلال بالقوانين أمكن للمجلس توقيع عقوبات مالية على أعوانها ، إلا أن مجلس المحاسبة كهيئة يبقى يحتاج لتوسيع أكثر لمدى استقلالية مهامه في إطار فصل السلطات لأجل القيام بمهمته الدستورية على أكمل وجه . الكلمات المفتاحية: مجلس المحاسبة، مكافحة الفساد، إجراءات الرقابة المالية Abstract: The Algerian Court of Accounts is a newly established supreme body for financial control, established by Law 80-05 based on the 1976 constitution, granting the powers of financial accounting control in order to supervise the oversight of the financial business of public institutions and administrations that the law grants it to follow up. This authority is double between judicial and administrative. To amend the text related to it in 1990 and abolish judicial oversight from the tasks entrusted to it, and the 1995 amendment came with the text of Ordinance 95-20 in force to this day, which restored him to exercise judicial oversight, which was expanded by the 2010 amendment and then the 2016 constitutional amendment and affirmed its constitutionality as an institution with broad powers in Financial Supervision, the last constitutional amendment 2020, according to Article 199 of it. It is an institution that enjoys financial and administrative independence, and all public institutions, within the framework of the system of legal texts in force, are subject to its obligatory control, with the obligation to submit their annual financial accounts before it. The independence of his duties within the framework of the separation of powers in order to carry out his constitutional mission to the fullest. Keywords: Accounting Council, anti-corruption, financial control procedures
Keywords: مجلس المحاسبة، مكافحة الفساد، إجراءات الرقابة المالية